PENGARUH LITERASI KEUNGAN DIGITAL DAN RESIKO TRANSAKSI DIGITAL TERHADAP MINAT PELAKU UMKM DALAM BERTRANSAKSI MENGGUNAKAN QRIS - Firdaus, Fiqri Maulana; Muiz, Abdul; Nasir, Abdul (Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to analyze the influence of digital financial literacy and digital transaction risk on the interest of Micro, Small, and Medium Enterprises (MSMEs) in transacting using QRIS (Quick Response Code Indonesian Standard). QRIS is one of the digital payment tools that is increasingly popular in Indonesia because of its convenience. However, the adoption of this technology still faces various challenges, such as low digital financial literacy and concerns about the risks of digital transactions. This study uses a quantitative approach with a survey method for MSME actors in the Perumnas Market, Cirebon City. The data was analyzed using multiple linear regression to determine the relationship between digital financial literacy, digital transaction risk perception, and interest in using QRIS. The results of the study show that digital financial literacy has a positive and insignificant effect on MSMEs' interest in using QRIS. The higher the digital financial literacy, the greater the interest of MSME actors in using QRIS. On the other hand, the risk of digital transactions has a positive and significant influence on interest in using QRIS. MSME actors who feel that the risk of digital transactions is high tend to be reluctant to use QRIS. The implications of this study are the importance of increasing digital financial literacy for MSME actors and the need for digital transaction risk management to increase the adoption of QRIS as a means of payment. Keywords: Digital financial literacy, digital transaction risk, user interest, MSMEs, QRIS.